“Socio cognitive factors involved in the teaching learning process in English language” - Pilatuña Ushpa, Rita Yolanda (2022)
Nowadays, English language learning is an important part of education because it allows us to have access to updated information. However, teaching is not an easy process, so some researchers in the area are looking for new methods and strategies that favour students in the process of teaching and learning English. On the other hand, this research project entitled "Socio-cognitive factors involved in the English language teaching-learning process"refers to the problems that teachers and students have during this process. When teaching a new language, students have difficulties that are not only related to academic performance, but are also influenced by other factors. This occurs because teachers are unaware of the social and cognitive aspects that affect the teaching-learning process of their students. Thus, the main objective of this research is to determine the influence of social-cognitive factors on the English language teaching-learning process. Therefore, this research project has been divided into two parts: the first part is based on a literature review on socio-cognitive factors and how they influence the teaching-learning process. The second part presents the results obtained from the surveys applied to the students of the first semester of the PINE of the Technical University of Cotopaxi, in Latacunga city. Based on the descriptive-qualitative method, the technique applied for this study was a student survey using a questionnaire as an instrument. It was adapted from the socio-cognitive theory: (Bandura, 1986); Multiple Intelligence: (H. Gardner, 1999) where thirty-five students participated. The analysis of the theoretical references exposed within the theoretical framework, it was possible to identify that different socio-cognitive factors that affected the process such as: the physical environment, the teacher-student relationship, didactic resources, family (motivation), economic level, culture, memory capacity, perception and attention. The outcomes of the survey showed how social and cognitive factors affect the teaching-learning process of the aforementioned students, as well as identifying those with the greatest impact on the educational environment. Therefore, it is essential for both students and teachers to know which factors can affect or favour the educational processes in order to build an adequate environment in the institutions.